Development of Canva Application-Based Animated Video Learning Media on Volleyball Passing Material at Junior High School - Traindini, Aditya Anya; Usra, Meirizal; Bayu, Wahyu Indra; Hartati; Yusfi, Herri; Ramadhan, Arizky (Jurnal Moderasi Olahraga, 2024)
This study aims to develop animated video-based learning media using the Canva application on volleyball passing material for Junior High School students. The development of this media is expected to facilitate a more effective, interactive, and interesting learning process for students. This research uses the Research and Development (R&D) method with the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The development results show that this animated video media meets the criteria of validity, effectiveness, and applicability based on the assessment of material experts, media experts, and trials to students. The trial shows an increase in students' understanding of volleyball passing techniques, which is reflected in the improvement of students' learning outcomes after using the learning media. In addition, the use of Canva as an animation video creation platform proved to be efficient in producing creative and accessible media. In conclusion, this Canva-based animated video learning media is effective in improving students' understanding of volleyball passing material. This media can be implemented in the PE learning process at school and is recommended to be further developed in other sports materials